2011
DOI: 10.1099/vir.0.031856-0
|View full text |Cite
|
Sign up to set email alerts
|

The ADP-ribose-1″-monophosphatase domains of severe acute respiratory syndrome coronavirus and human coronavirus 229E mediate resistance to antiviral interferon responses

Abstract: Several plus-strand RNA viruses encode proteins containing macrodomains. These domains possess ADP-ribose-10-phosphatase (ADRP) activity and/or bind poly(ADP-ribose), poly(A) or poly(G). The relevance of these activities in the viral life cycle has not yet been resolved. Here, we report that genetically engineered mutants of severe acute respiratory syndrome coronavirus (SARS-CoV) and human coronavirus 229E (HCoV-229E) expressing ADRP-deficient macrodomains displayed an increased sensitivity to the antiviral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 42 publications
9
119
1
1
Order By: Relevance
“…4E and Table 2) (4648). The activity of this domain is not essential for replication in vitro but may help counteract the innate immune response in vivo (49, 50). At approximately the same position of snake virus pp1a is a predicted protein kinase (PFam PKinase domain) that is not present in any other nidovirus as determined by HMMER analysis (HMMER3 E value, 1.5 × 10 −6 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4E and Table 2) (4648). The activity of this domain is not essential for replication in vitro but may help counteract the innate immune response in vivo (49, 50). At approximately the same position of snake virus pp1a is a predicted protein kinase (PFam PKinase domain) that is not present in any other nidovirus as determined by HMMER analysis (HMMER3 E value, 1.5 × 10 −6 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has shown that the X domain (Mac1) is dispensable for RNA replication in the context of a SARS-CoV replicon (Kusov et al, 2015). Recently, evidence accumulated showing that the X domain plays a role in counteracting the host innate immune response (Eriksson et al, 2008;Kuri et al, 2011;Fehr et al, , 2016.…”
Section: Macrodomain I (Mac1 X Domain)mentioning
confidence: 99%
“…These results suggest that the main function of the X domain may differ in different CoVs. On the other hand, the expression level of type-I IFN (α or β) is increased in cells infected with SARS-CoV or MHV carrying the Asn-to-Ala mutation in the X domain (Eriksson et al, 2008;Kuri et al, 2011;Fehr et al, 2016). This indicates that suppression of innate immunity by the X domain may be a feature conserved across the coronaviruses.…”
Section: Macrodomain I (Mac1 X Domain)mentioning
confidence: 99%
“…In addition to the nsps mentioned above, other CoV nsps are involved in RNA binding (nsp9 and nsp10; [48,49]) or in evasion of the antiviral response of the host (nsp1 and nsp3; [50,51,52,53,54,55,56,57]). The function of nsp2 is not yet known, although this protein was shown not to be essential for virus replication [58,59].…”
Section: Coronavirus Nonstructural Proteinsmentioning
confidence: 99%